Metaverse in education in the era society 5.0: A systematic literature review - Niken Vintang Erdwiyana; Ade Ilham Fadhilah; Fairuz Basman Siddiq Bukhori (Hipkin Journal of Educational Research, 2024)
Metaverse emerged as a key concept in the Age of Society 5.0. The metaverse has the potential to be particularly relevant in distance education to overcome limitations as a two-dimensional web learning tool. This research aims to explore the utilization of the metaverse in education, highlighting the distribution of studies by year, country, field, type of research, and technological context. The approach used in this study is SLR (Systematic Literature Review). The library sources used are sourced from 5 academic studies that have been indexed by Scopus. The results showed that the metaverse can create a participatory and continuous learning environment, the efficiency of the learning process can be maximized, facilitate synchronous and asynchronous learning, as well as the flipped classroom method and fun cooperative learning to provide motivation and cooperation. In conclusion, the development of the metaverse in education reflects the dynamics of technological changes and the demands of the society 5.0 era. With the continued development of metaverse technology, future research is expected to provide deeper insights into how the metaverse contributes significantly to achieving learning goals in an era that is increasingly integrated between the virtual world and the physical world.    Abstrak Metaverse muncul sebagai konsep kunci dalam Era Society 5.0. Metaverse memiliki potensi sangat relevan dalam pendidikan jarak jauh untuk mengatasi batasan sebagai alat pembelajaran web dua dimensi. Penelitian ini bertujuan menggali pemanfaatan metaverse dalam pendidikan, menyoroti distribusi studi berdasarkan tahun, negara, bidang, jenis penelitian, dan konteks teknologi. Pendekatan yang digunakan pada penelitian ini adalah SLR (Systematic Literature Review). Adapun sumber pustaka yang digunakan bersumber dari lima studi akademis yang telah terindeks scopus. hasil penelitian menunjukkan bahwa metaverse dapat menciptakan lingkungan pembelajaran yang partisipatif dan berkelanjutan, efisiensi proses pembelajaran dapat dimaksimalkan, memfasilitasi pembelajaran sinkron dan asinkron, serta metode kelas terbalik dan pembelajaran kooperatif yang menyenangkan untuk memberikan motivasi dan kerja sama. Sebagai kesimpulan, perkembangan metaverse dalam pendidikan mencerminkan dinamika perubahan teknologi dan tuntutan era society 5.0. Dengan terus berkembangnya teknologi metaverse, penelitian di masa depan diharapkan dapat memberikan wawasan lebih mendalam tentang bagaimana metaverse berkontribusi nyata dalam mencapai tujuan pembelajaran di era yang semakin terintegrasi antara dunia maya dan dunia fisik. Kata Kunci: systematic literature review; metaverse; society 5.0; pendidikan